The influence of asphalt mixture on rutting properties using pet (polyethylene terephthalate) as additive in flexible pavement - Siti Norafzan, Dahkimau (2014)
Most plastic collected for recycling from the household waste stream and the majority plastic bottle come from Polyethylene Terephthalate (PET). Rutting or permanent deformation is one of the most important failure mechanisms in asphalt pavement. The objective of this study is to determine the rutting of asphalt mixture. The bitumen content used in binder course is 5%. The range of percentage addictive of PET into asphalt mixture is up to 10% that were calculated and assessed with the laboratory test. There are two type of mineral filler used which Portland cement and lime for both control and modified asphalt. To evaluate the rutting of asphalt mixture, the samples were subjected to Repeated Load Axial Test (RLAT) loading for 1800 cycles and axial load applied 1OOkn. RLAT is common testing method in laboratory to measure the resistance to rutting of asphalt mixture. The finding indicates that rutting occurs at the highest percentage of PET addition which 10%. It means that PET was improved the rutting properties on asphalt mixture. In term of economic aspect, the PET could reduce cost of road construction because this material is cheaper than bitumen and easy to get. The outcome shows, addition of PET modified asphalt mixture can resist road failures as well as it increase the level of performance and the service life of the road. For the environmental consideration, PET modified asphalt is most suitable to be used for road pavements. It can be conclude that, the PET modified asphalt gives more advantages compared to the conventional method.